Littérature Française et Savoirs Biologiques Au XIXe Siècle : Traduction, Transmission, Transposition. - Klinkert, Thomas. (Mimesis Series, 2019)
With its new sub-title Romance Literatures of the World, the book series Mimesis presents an innovative and integral understanding of the Romance world and Romance Studies from the perspective of literary studies and cultural theory. It takes account of the fact that the fascinating development of Romance literatures and cultures both in Europe and beyond has set worldwide dynamics in motion which continue the great traditions of the Romance world and open up new horizons for them. Mimesis works from a transareal understanding of Romance Studies which integrates Romance literatures and cultures both within and outside Europe and which transcends the national and disciplinary boundaries which often conceal the interactions between different traditions and developments in Europe and the Americas, in Africa and Asia. In the archipelago of Romance Studies, Mimesis reveals how the representation of reality in the Romance literatures of the world opens the door to a multilingual cosmos of diverse logics.